Carbon composite tin phosphide material and preparation and application thereof
The new carbon composite tin phosphide material was prepared by hydrothermal method-chemical vapor deposition, which solved the problems of powderization and poor conductivity of tin phosphide materials during the charge and discharge cycle, and achieved high electrochemical performance and suitable for large-scale production.
Patent Information
- Application Number
- CN202311086004.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-08-24
AI Technical Summary
Tin phosphide materials are prone to powder during the charge and discharge cycle, resulting in a decrease in cycle life and poor conductivity, affecting the magnification cycle performance.
The new carbon composite tin phosphide material was prepared by hydrothermal method-chemical vapor deposition. Inexpensive materials such as sodium tartrate, sodium alginate, sodium citrate, tin tetrachloride, acetylene black were used to form a particle structure with a particle size of 30-100 nm, and phosphating and carbonizing were performed by chemical vapor deposition.
The electrochemical performance of the material is improved. As the negative electrode material of sodium ion battery, the discharge specific capacity under the current density of 2A g-1 is still as high as 143mAhg-1, and the preparation process is simple and controllable, suitable for large-scale production.
Smart Images

Figure HDA0004416080450000011 
Figure HDA0004416080450000012 
Figure HDA0004416080450000013
Abstract
Description
Technical Field
[0001] The present application relates to a novel carbon composite tin phosphide material and its application, belonging to the field of inorganic material preparation and electrochemical technology. Background Art
[0002] Tin phosphide (Sn4P3) is a layered semiconductor material composed of alternating layers of phosphorus atoms and tin atoms. It has good electrochemical activity for sodium ions, especially for Li + 、Na + Plasma ion embedding / extraction. This material has a high theoretical specific capacity and good cycle reversibility, and has therefore attracted the attention of many researchers recently. At the same time, the material precursor is cheap and the preparation process is relatively simple, which is particularly conducive to large-scale production. However, in practical applications, the material is prone to volume expansion and pulverization during the charge and discharge cycle, resulting in a reduced cycle life of the material; at the same time, the material has poor conductivity, resulting in poor rate cycling performance of the material. To solve this problem, most researchers focus on coating the surface of the material with carbon materials or compounding it with other materials, such as with graphene materials. However, this will not only increase the preparation cost of the material, but the additional coating or compounding components will also reduce the specific capacity of the material. Summary of the invention
[0003] The purpose of the present application is to provide a novel carbon composite tin phosphide material in order to avoid the deficiencies of the above-mentioned prior art.
[0004] According to one aspect of the present application, a method for preparing a novel carbon composite tin phosphide material is provided. The novel carbon composite tin phosphide material is a particle structure with a particle size of 30 to 100 nm.
[0005] The novel carbon composite tin phosphide material is prepared by a hydrothermal method-chemical vapor deposition method. The specific preparation method is as follows:
[0006] Dissolve at least one of sodium tartrate, sodium alginate, and sodium citrate in deionized water, then add at least one of tin tetrachloride and stannous dichloride, and stir to completely dissolve to form a solution. Then add at least one of acetylene black and activated carbon and stir evenly. Subsequently, add sodium hydroxide, stir for 10 to 30 minutes, and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 120-180°C for 6 to 12 hours. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, use a centrifuge to wash the obtained product with deionized water 3 to 4 times, collect the precipitate, and dry it at 60 to 80°C for 6 to 12 hours to obtain a precursor. The obtained precursor material is placed in a crucible and placed in a tubular furnace, and at least one of sodium hypophosphite and red phosphorus is used as a phosphorus source, and the precursor material is phosphated and carbonized using a chemical vapor deposition method.
[0007] The concentration of sodium tartrate, sodium alginate and sodium citrate in the solution is 1 mg mL -1 ~50mg mL -1 ;
[0008] The concentration of tin tetrachloride and stannous dichloride in the solution is 1 mg mL -1 ~100mg mL -1 ;
[0009] The concentration of acetylene black and activated carbon in the solution is 0.01 mg mL -1 ~10mg mL -1 .
[0010] The mass ratio of the sodium hypophosphite, red phosphorus and the precursor after hydrothermal reaction is 0.1:1 to 10:1.
[0011] The temperature of the chemical vapor deposition method is 300-400° C. and the time is 2-4 hours.
[0012] Optionally, the concentration of sodium tartrate, sodium alginate, and sodium citrate in the solution is selected from 1 mg mL -1 , 5mg mL -1 , 12mg mL -1 , 20mg mL -1 , 35mg mL -1 , 45mg mL -1 , 50mg mL -1 Any value in or a range of values between any two of the above points.
[0013] Optionally, the concentration of tin tetrachloride and stannous dichloride in the solution is selected from 1 mg mL -1 , 20mg mL -1 , 50mg mL -1 , 80mg mL -1 , 100mg mL -1 Any value in or a range of values between any two of the above points.
[0014] Optionally, the concentration of acetylene black and activated carbon in the solution is selected from 0.01 mg mL -1 , 0.1mg mL -1 , 0.5mgmL -1 , 1mg mL -1 , 2mg mL -1 , 6mg mL -1 , 10mg mL -1 Any value in or a range of values between any two of the above points.
[0015] Optionally, the mass ratio of the sodium hypophosphite, red phosphorus and the precursor after hydrothermal reaction is selected from any value of 0.1:1, 1:1, 3:1, 5:1, 8:1, 10:1 or a range between any two of the above points.
[0016] According to another aspect of the present application, the material prepared in the present application is used as a negative electrode material for a sodium ion battery, and a method for preparing an electrode using the material as a negative electrode active material is provided. The specific preparation method is as follows:
[0017] Weigh a certain amount of prepared carbon composite tin phosphide material, mix it with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1 to 7:1.5:1.5, grind it thoroughly, add an appropriate amount of N-methyl-2-pyrrolidone with a dropper, stir it thoroughly to form a paste, apply the mixed electrode material on the carbon-coated aluminum foil, and then use a blast drying oven to dry it at 60 to 80 ° C for 4 to 6 hours. Then use the electrode to assemble a sodium ion battery. Then use the LAND-CT2001A battery test system to test the electrochemical performance of the prepared battery.
[0018] The test results show that the battery using carbon composite tin phosphide as the negative electrode active material has excellent electrochemical performance. When used as the negative electrode material of sodium ion battery, 2A g -1 The discharge capacity of the battery is still as high as 143 mAh g at the current density -1 The excellent electrochemical performance shows that it has great application prospects. At the same time, the preparation process is simple and controllable, and the equipment is simple, which is a method that is easy to carry out large-scale production.
[0019] The excellent electrochemical performance of the novel carbon composite tin phosphide material in this application indicates that it has great application prospects as a negative electrode material for sodium ion batteries. At the same time, the preparation process of this novel carbon composite tin phosphide material is simple and controllable, and the equipment is simple, which is a method that is easy to carry out large-scale production.
[0020] The beneficial effects of this application include:
[0021] 1) The raw materials used in the present invention are cheap materials such as sodium alginate, tin tetrachloride, acetylene black, etc. The materials are widely available, green, safe and low in cost.
[0022] 2) The preparation method of the present invention is simple and can be used for large-scale production.
[0023] 3) The novel carbon composite tin phosphide material obtained by the present invention has broad application prospects and can be used as a negative electrode material for sodium ion batteries and has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1This is a SEM picture of the carbon composite tin phosphide material of the present application.
[0025] Figure 2 The carbon composite tin phosphide material prepared in this application is used as the negative electrode of the sodium ion battery at 0.1A g -1 Discharge voltage platform diagram under current density of .
[0026] Figure 3 This is a rate cycle curve diagram of the carbon composite tin phosphide material prepared in this application when used as the negative electrode of a sodium ion battery. DETAILED DESCRIPTION
[0027] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0028] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0029] The carbon composite tin phosphide material was scanned using a JSM-7800F scanning electron microscope.
[0030] The electrochemical performance test was carried out using the Blue Battery Test System.
[0031] The present invention is a method for preparing a carbon composite tin phosphide material, comprising the following steps:
[0032] Dissolve at least one of sodium tartrate, sodium alginate, and sodium citrate in deionized water, then add at least one of tin tetrachloride and stannous dichloride, and stir to completely dissolve to form a solution. Then add at least one of acetylene black and activated carbon and stir evenly. Subsequently, add sodium hydroxide, stir for 10 to 30 minutes, and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 120-180°C for 6 to 12 hours. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, use a centrifuge to wash the obtained product with deionized water for 3 to 4 times, collect the precipitate, and dry it at 60 to 80°C for 6 to 12 hours to obtain a precursor. The obtained precursor material is placed in a crucible and placed in a tubular furnace, and at least one of sodium hypophosphite and red phosphorus is used as a phosphorus source, and the precursor material is phosphated and carbonized using a chemical vapor deposition method.
[0033] Weigh a certain amount of prepared carbon composite tin phosphide material, mix it with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1 to 7:1.5:1.5, grind it thoroughly, add an appropriate amount of N-methyl-2-pyrrolidone with a dropper, stir it thoroughly to form a paste, coat the mixed electrode material on the nickel foam, and then use a blast drying oven to dry it at 60 to 80 ° C for 4 to 6 hours. Then use the electrode to assemble sodium ion batteries respectively. Then use the LAND-CT2001A battery test system to test the electrochemical performance of the prepared battery.
[0034] Preparation Example 1
[0035] Weigh 0.1 g of the prepared carbon composite tin phosphide material, mix it with conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:1:1 and grind it thoroughly. Then, add 2 mL of N-methyl-2-pyrrolidone with a dropper and stir thoroughly to form a paste. Then, coat the mixed electrode material on nickel foam with a loading of 1-3 mg cm -2 (Here 2.6 mg cm -2 ), the electrode is a disc with a diameter of 1.6 cm and a thickness of about 70-100 microns (here 92 microns), and then dried in a blast drying oven at 60-80°C (here 70°C) for 4-6 hours (here 5 hours). The electrodes were then used to assemble sodium ion batteries, with the counter electrode being a sodium sheet, the diaphragm being a glass fiber membrane, and the electrolyte being 1M NaClO4 / DC (diethyl carbonate): EC (ethylene carbonate): DMC (dimethyl carbonate) = 1:1:1. The prepared battery was then subjected to electrochemical performance testing using the LAND-CT2001A battery testing system, constant current and rate charge and discharge testing, with current densities of 0.1A g -1 ; 0.1, 0.2, 0.3, 0.5, 1, 2 and 0.03A g -1 .
[0036] Example 1
[0037] Dissolve 0.1g of sodium alginate in 50mL of deionized water, then add 0.71g of tin tetrachloride and stir to completely dissolve it to form a solution. Then add 0.1g of acetylene black and stir evenly. Subsequently, add 0.16g of sodium hydroxide, stir for 20 minutes, and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 150°C for 8h. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, use a centrifuge to wash the obtained product with deionized water 3 times, collect the precipitate, and dry it at 60°C for 8h to obtain the precursor.
[0038] The obtained precursor material is placed in a crucible and put into a tubular furnace, and sodium hypophosphite is used as a phosphorus source and placed in front of the precursor material (along the flow direction of nitrogen, nitrogen flows through the phosphorus source and the precursor material in turn). The precursor material is phosphated and carbonized using chemical vapor deposition in a nitrogen atmosphere at a temperature of 350°C for 4 hours.
[0039] The carbon composite tin phosphide material prepared according to the above steps was used as the active material, and the electrode prepared according to the process of Preparation Example 1 was used as the negative electrode, and assembled into a sodium ion battery. The prepared battery was then subjected to electrochemical performance testing using a blue battery test system.
[0040] Figure 1 The SEM image of the prepared carbon composite tin phosphide material shows that the material has a particle structure with a particle size of 30 to 100 nm and good crystallinity.
[0041] Figure 2 The carbon composite tin phosphide material prepared in this application is used as the negative electrode of the sodium ion battery at 0.1A g -1 The discharge voltage platform diagram under the current density of . It can be clearly seen from Figure 2 that the discharge voltage of the battery is 0.4V.
[0042] Figure 3 This is a rate cycle curve of the carbon composite tin phosphide material prepared in this application as the negative electrode of a sodium ion battery. Figure 3 As can be seen, 2Ag -1 The battery discharge capacity can still reach 143mAh g -1 .
[0043] Example 2
[0044] Dissolve 0.1g sodium citrate in 50mL deionized water, then add 0.71g tin tetrachloride and stir to completely dissolve to form a solution. Then add 0.1g activated carbon and stir evenly. Subsequently, add 0.16g sodium hydroxide, stir for 20 minutes and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 150°C for 8h. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, the obtained product is washed with deionized water three times using a centrifuge and the precipitate is collected. After drying at 60°C for 8h, the precursor is obtained. The obtained precursor material is placed in a crucible and placed in a tubular furnace, and red phosphorus is used as the phosphorus source, placed in front of the precursor material, and the precursor material is phosphorus-carbonized using chemical vapor deposition in a nitrogen atmosphere at a temperature of 350°C for 4h.
[0045] The carbon composite tin phosphide material prepared according to the above steps was used as the active material, and the electrode prepared according to the process of Preparation Example 1 was used as the negative electrode to assemble a sodium ion battery. The prepared battery was then subjected to electrochemical performance testing using a blue battery test system.
[0046] The method used in Example 2 is basically the same as that in Example 1, except that sodium alginate is replaced by sodium citrate, acetylene black is replaced by activated carbon, and the phosphorus source is replaced by red phosphorus instead of sodium hypophosphite. The electrochemical test results show that the performance of the carbon composite tin phosphide material prepared by this method is basically the same as that of Example 1, 2Ag -1 The battery discharge capacity can still reach 140mAh g -1 This is because within a certain range, the performance of carbon composite tin phosphide materials is independent of the types of sodium salt, carbon source, and phosphorus source.
[0047] Comparative Example 1
[0048] Dissolve 0.1g of sodium alginate in 50mL of deionized water, then add 0.71g of tin tetrachloride and stir to completely dissolve it to form a solution. Subsequently, add 0.16g of sodium hydroxide, stir for 20 minutes and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 150°C for 8h. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, the obtained product is washed with deionized water three times using a centrifuge and the precipitate is collected. After drying at 60°C for 8h, the precursor is obtained. The obtained precursor material is placed in a crucible and placed in a tubular furnace, and sodium hypophosphite is used as a phosphorus source and placed in front of the precursor material. The precursor material is phosphated and carbonized using chemical vapor deposition in a nitrogen atmosphere at a temperature of 350°C for 4h.
[0049] The carbon composite tin phosphide material prepared according to the above steps was used as the active material, and the electrode prepared according to the process of Preparation Example 1 was used as the negative electrode to assemble a sodium ion battery. The prepared battery was then subjected to electrochemical performance testing using a blue battery test system.
[0050] Comparative Example 1 is basically the same as the method used in Example 1, except that acetylene black is not added during the material preparation process. The electrochemical test results show that the performance of the carbon composite tin phosphide material prepared by this method is significantly lower than that of Example 1 in terms of rate discharge specific capacity, and 2Ag -1 The battery discharge capacity is only 98 mAh g -1 This is because composite acetylene black can enhance the conductivity and cycle stability of the material, and its use or not will significantly affect the discharge performance of the composite material.
[0051] Comparative Example 2
[0052] Dissolve 0.71g of tin tetrachloride in 50mL of deionized water and stir to completely dissolve to form a solution. Then add 0.1g of acetylene black and stir evenly. Subsequently, add 0.16g of sodium hydroxide, stir for 20 minutes, and transfer the mixed solution to a reactor lined with polytetrafluoroethylene. React at 150°C for 8h. After that, after the temperature drops to room temperature, use a centrifuge to collect the white precipitate. After that, the obtained product is washed 3 times with deionized water using a centrifuge and the precipitate is collected. After drying at 60°C for 8h, the precursor is obtained. The obtained precursor material is placed in a crucible and placed in a tubular furnace, and sodium hypophosphite is used as a phosphorus source and placed in front of the precursor material. The precursor material is phosphated and carbonized using chemical vapor deposition in a nitrogen atmosphere at a temperature of 350°C for 4h.
[0053] The carbon composite tin phosphide material prepared according to the above steps was used as the active material, and the electrode prepared according to the process of Preparation Example 1 was used as the negative electrode to assemble a sodium ion battery. The prepared battery was then subjected to electrochemical performance testing using a blue battery test system.
[0054] Comparative Example 2 is basically the same as the method used in Example 1, except that sodium alginate is not added during the material preparation process. The electrochemical test results show that the performance of the carbon composite tin phosphide material prepared by this method is significantly lower than that of Example 1 in terms of rate discharge specific capacity. -1 The battery discharge capacity is only 110 mAh g -1 This is because the use of sodium alginate can inhibit crystal growth during the preparation of tin phosphide precursors, thereby increasing the specific surface area of the material, and the carbonization of sodium alginate can enhance the conductivity and cycle stability of the material. Its use or not will significantly affect the discharge performance of the composite material.
[0055] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for preparing a carbon composite tin phosphide material, characterized in that: The material is prepared by a hydrothermal method-chemical vapor deposition method; the specific process is: 1) Hydrothermal reaction: dissolve at least one or two of sodium tartarate, sodium alginate and sodium citrate in water, then add at least one or two of tin tetrachloride and stannous dichloride, stir to completely dissolve to form a solution; then add at least one or two of acetylene black and activated carbon and stir evenly; then, add sodium hydroxide, stir (preferably for 10 to 30 minutes) and transfer the mixed solution to a reactor; react at 120-180° C. for 6 to 12 hours; then, after the temperature drops to room temperature, separate the solid and liquid (such as by centrifugation) and collect the precipitate; then, wash the obtained precipitate with water for 3 to 4 times, and dry it at 60 to 80° C. for 6 to 12 hours to obtain a precursor; 2) Chemical vapor deposition method: The obtained precursor material is placed in a tube furnace, and at least one or two or more of sodium hypophosphite and red phosphorus are used as phosphorus sources, and the precursor material is phosphated and carbonized by chemical vapor deposition method.
2. The preparation method according to claim 1, characterized in that: The concentration of at least one or more of sodium tartrate, sodium alginate and sodium citrate in water in the solution is 1 mg / mL -1 ~50mg mL -1 , preferably 5 mg mL -1 ~20mg mL -1 ; The concentration of at least one or both of tin tetrachloride and stannous dichloride in the aqueous solution is 1 mg mL -1 ~100mg mL -1 , preferably 10 mg mL -1 ~30 mg mL -1 ; The concentration of at least one or both of acetylene black and activated carbon in the aqueous solution is 0.01 mg mL -1 ~10mg mL -1 , preferably 1 mg mL -1 ~5mg mL -1 .
3. The preparation method according to claim 1, characterized in that: The concentration of sodium hydroxide added was 0.25 mg mL -1 ~25mg mL -1 , preferably 2 mg mL -1 ~10mg mL -1 .
4. The preparation method according to claims 1-3, characterized in that: The mass ratio of the phosphorus source to the precursor after the hydrothermal reaction is 0.1:1-10:1, preferably 1:1-3:1; the temperature of the chemical vapor deposition method is 300-400°C, and the time is 2-4h.
5. A carbon composite tin phosphide material prepared by the preparation method according to any one of claims 1 to 4.
6. The carbon composite tin phosphide material according to claim 5, characterized in that: The carbon composite tin phosphide material is a particle structure with a particle size of 30 to 100 nm.
7. Use of the carbon composite tin phosphide material according to any one of claims 5 to 6 as a negative electrode active material for a sodium ion battery.
8. The use according to claim 7, characterized in that: The sodium ion battery comprises a positive electrode, a diaphragm, a negative electrode arranged in sequence, and a diaphragm electrolyte filled between the positive electrode and the negative electrode.
Citation Information
Patent Citations
Tin-phosphide composite material and preparation method and application thereof
CN110034283A
Preparation method of novel nano-structure tin-carbon composite negative electrode material
CN112436127A
High-performance sodium ion battery negative electrode material and preparation method thereof
CN116443862A